Integral calculus on Eq(2) - Brzeziński, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
The complexes of integral forms on the quantum Euclidean group Eq(2) and the quantum plane are defined and their isomorphisms with the corresponding de Rham complexes are established.